Driving sustained competitive advantage through agility, NDP and innovation for telecommunication service providers. (10th December 2019) - Muthu, Devandran; Thangavelu, Indra
With the emergence of the digital economy and shorter product/service life cycles, advancing knowledge in the field of sustained competitive advantage has become more urgent. The research framework was formulated with: 1) the constructs firm agility (alertness, accessibility, decisiveness, swiftness, flexibility); 2) new product development (design thinking, human-computer interaction, design engineering, software development); 3) innovation (magnitude and speed), with the focal construct sustained competitive advantage to achieve customer retention mediated by customer loyalty. This was a quantitative study and analysed using SPSS and Smart Pls 3. The findings revealed the three construct had positive relationship with the focal and the mediator significantly effected the focal towards achieving customer retention. The results of this study imply that merely creating sustained competitive advantage is inadequate to retain customers without first creating customer loyalty. This study provides better understanding to managers and business owners as they formulate strategies toward growth and improved financial performances.